Transition metal dichalcogenide for high-performance electrode of supercapacitor - Saifful Kamaluddin, Muzakir; Ahmad Salihin, Samsudin; Bouchta, Sahraoui (2018)
Molybdenum dichalcogenides have been reviewed from the perspectives of bandgap, conductivity, and oxidation states of transition metal. Researchers have concluded that a narrow-bandgap transition metal dichalcogenide with high conductivity could be achieved for the high-performance electrode of a supercapacitor.